1999
DOI: 10.5465/256972
|View full text |Cite
|
Sign up to set email alerts
|

Does Stakeholder Orientation Matter? The Relationship Between Stakeholder Management Models and Firm Financial Performance

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
356
4
14

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 573 publications
(384 citation statements)
references
References 59 publications
10
356
4
14
Order By: Relevance
“…Governments play a prominent institutional role in CEM practices and are referred to in both institutional and environmental research (e.g., Berman et al 1999;Hoffman 2001;Shrivastava 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Governments play a prominent institutional role in CEM practices and are referred to in both institutional and environmental research (e.g., Berman et al 1999;Hoffman 2001;Shrivastava 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Covin&Slevin (1989) investigated the effective strategic responses to environmental hostility among 161 small manufacturing firms and found that in such an environment there was a positive relationship between small firms' performance and their organic structure, entrepreneurial strategic posture, competitive profile characterized by a long-term orientation, high product prices, and concern towards predicting industry trends. Berman et al (1999) empirically researched the effect of stakeholder management on corporate performance, and they found support for a strategic stakeholder management model but no support for an intrinsic stakeholder commitment model. Based on surveys of U.S. and U.K. firms, Brouthers et al (2015) found that international performance of SMEs depended on entrepreneurial orientation (EO) and the type of alliance (research or marketing).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A recent literature review on this topic is provided by Beurden and Gössling (2008). However, the available evidence is inconclusive; there are some studies that have found a positive link (e.g., Waddock and Graves 1997), some have found a negative link (e.g., Konar and Cohen 2001), while others have found no link at all (e.g., Berman et al 1999). These conflicting findings have led researchers to look for more complex possibilities for the EP-FP relationship (Russo and Fouts 1997;Peloza 2006;Hull and Rothenberg 2008).…”
Section: Introductionmentioning
confidence: 99%